Alterations in brain iron and myelination in children with ASD: A susceptibility source separation imaging study - Xiang Zhou; Ya‑Yin Deng; Long Qian; Shuang‑Shuang Zhong; Feng‑Yun Zou; Li‑Shan Shen; Xiao‑Wen Luo; Bo-Ya Yin; Yi-Fan He; Ruo‑Mi Guo (NeuroImage)
Autism spectrum disorder (ASD) may have both brain iron and myelin changes, but traditional methods fail to differentiate them. This study utilized an advanced susceptibility source separation technique, APART-QSM (iterAtive magnetic suscePtibility sources sepARaTion), to investigate brain iron and myelination alterations in children with ASD and link neuroimaging findings to clinical symptom severity. Sixty-five school-aged children with ASD and Sixty age- and sex-matched typically developing children were included. By providing enhanced and broader detection capabilities compared to conventional QSM, APART-QSM uncovered reduced iron content across multiple deep gray matters and decreased myelin content in the globus pallidum in ASD. The iron and myelin contents in the globus pallidum and iron content in the substantia nigra were significantly negatively correlated with ASD symptom severity. Coexisting abnormal brain iron and myelin contents in ASD, particularly in the globus pallidus, offer innovative and promising insights into ASD pathology and potential biomarkers.